2022
DOI: 10.1155/2022/5831247
|View full text |Cite
|
Sign up to set email alerts
|

Redox Metabolism-Associated Molecular Classification of Clear Cell Renal Cell Carcinoma

Abstract: Clear cell renal cell carcinoma (ccRCC) is the most common subtype of renal cell carcinoma. Redox metabolism has been recognized as the hallmark of cancer. But the concrete role of redox-related genes in patient stratification of ccRCC remains unknown. Herein, we aimed to characterize the molecular features of ccRCC based on the redox gene expression profiles from The Cancer Genome Atlas. Differentially expressed redox genes (DERGs) and vital genes in metabolism regulation were identified and analyzed in the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 53 publications
1
4
0
Order By: Relevance
“…It can relay signals and activate MAPK, necessary for cell development, growth, survival, and differentiation [298]. Interestingly, our study found that KRAS is downregulated, and another study also concluded the same (Figure 3.27 c) [299].…”
Section: Erk Pathwaysupporting
confidence: 67%
“…It can relay signals and activate MAPK, necessary for cell development, growth, survival, and differentiation [298]. Interestingly, our study found that KRAS is downregulated, and another study also concluded the same (Figure 3.27 c) [299].…”
Section: Erk Pathwaysupporting
confidence: 67%
“…Metabolic signatures play a crucial role in tumor subclassification and immunotherapy response prediction. Some previous research had confirmed that metabolic signatures showed good power in tumor sub-phenotype and treatment response prediction in diffuse large B-cell lymphoma ( 61 ), ovarian ( 62 ) and colorectal cancers ( 63 ) as well as clear cell renal cell carcinoma ( 64 ). Chen et al.…”
Section: Discussionmentioning
confidence: 94%
“…Meanwhile, another study has shown that hypo-expression of ALDH6A1 was associated with survival of metastatic prostate cancer patients [ 31 ]. The downregulated ALDH6A1 has been proved to regulate the immune response in clear cell renal cell carcinoma, which implied a new biomarker for the clinical immunotherapy of ccRCC patients [ 32 ]. Our study is for the first time to figure out the drug-metabolism related gene ALDH6A1 expression was low in gastric cancer group.…”
Section: Discussionmentioning
confidence: 99%